Low-temperature reactive spark plasma sintering of dense SiC-Ti3SiC2 ceramics. Issue 4 (April 2023) - Podbolotov, Kirill; Moskovskikh, Dmitry; Abedi, Mohammad; Suvorova, Veronika; Nepapushev, Andrey; Ostrikov, Kostya (Ken); Khort, Alexander
Abstract: SiC-based ceramics are of great interest for various advanced applications. However, its fabrication requires high-temperature treatment at ∼2000 – 2100 °С. In this study, we developed an approach based on low-temperature reactive spark plasma sintering to produce dense SiC-based ceramics with superior mechanical properties. It was found that an SPS temperature of 1600 °C and introduction of 10 – 15 wt% of mechanically activated non-oxide Ti–Si–C additive is required to manufacture ceramics with a theoretical density of higher than 90%. Nonetheless, employing 5 – 15 wt% of the additive mixture and an SPS temperature of 1700 °C, the maximum density of ∼ 98% was achieved. The controlled formation and decomposition of the in-situ Ti3 SiC2 MAX phase enables the fabrication of the engineering ceramics with enhanced compressive strength (550 MPa), elastic modulus (485 GPa), and microhardness (32 GPa), which are comparable to the best-reported SiC ceramics. The study has a significant potential for practical application in the production of advanced SiC-based ceramics for various purposes and could be used for further understanding and development of the high-temperature sintering methods. Graphical Abstract: ga1 Highlights: Ball mill mixing activates raw addictive powder but doesn't affect its composition. Increasing SPS temperature to 1700 °C enhances SiC-based ceramics density. Increasing additive content to 15 wt% enables the fabrication of dense SiC ceramics. In situ Ti3 SiC2 MAX phase facilitates the formation of nanocomposite ceramic structure. SiC ceramics with in situ Ti3 SiC2 additive shows superior mechanical characteristics.